Change of East-Asian Summer Precipitation Associated With Strong El Niño Under the Future Emission Scenarios - Huang, Yu; Ren, Hong-Li; Liu, Minghong (Frontiers in Earth Science, 2021)
Strong Eastern-Pacific type El Niño (EP-El Niño) events have significant impacts on the decaying-summer precipitation over East Asia (EA). It has been demonstrated that frequency of strong EP-El Niños will increase and associated precipitation will become more severe and complex under future high emission scenarios. In this study, using simulations of CMIP5 and CMIP6, changes of the summer precipitation pattern related to strong EP-El Niño during its decay phase and the possible mechanism as responding to high emission scenarios are examined. Precipitation anomaly patterns over EA of strong EP events show a large inter-model spread in historical simulations between the CMIP models where CMIP6 is not superior to CMIP5. Under high emission scenarios, changes of summer precipitation anomalies related to strong EP events tend to increase over the southern EA and decrease around the northern EA from CMIP5, while there is an overall increase in the whole EA from CMIP6. The common change is featured by the increase of precipitation over southeastern China under high emission scenarios. This could be mainly attributed to the anticyclonic circulation from the South China Sea to the western North Pacific as a delayed response to more frequent strong EP-El Niños, which favors an increase in water vapor fluxes converging into the southeastern China.